The evolving international investment regime: expectations, realities, options - Alvarez, José E.; Sauvant, Karl P. (New York, 2011)
"With the growth of the global economy over the past two decades, foreign direct investment (FDI) laws, at both the national and international levels, have undergone rapid development in order to strengthen the protection standards for foreign investors. In terms of international investment law, a network of international investment agreements has arisen as a way to address FDI growth. FDI backlash, reflective of more restrictive regulation, has also emerged. The Evolving International Investment Regime analyzes the existing challenges to the international investment regime, and addresses these challenges going forward. It also examines the dynamics of the international regime, as well as a broader view of the changing global economic reality both in the United States and in other countries. The content for the book is a compendium of articles by leading thinkers, originating from the International Investment Conference "What's New in International Investment Law and Policy?""